2022
DOI: 10.1186/s12879-022-07225-5
|View full text |Cite
|
Sign up to set email alerts
|

Human rhinoviruses prevailed among children in the setting of wearing face masks in Shanghai, 2020

Abstract: Background Human rhinovirus (HRV) is the predominant etiological agent of the common cold in children and adults. A recent study showed that the inhibitory effect of face masks on viral shedding of HRV was less prominent than that on other respiratory viruses. Considering that most Chinese people have worn face masks in public area since the outbreak of coronavirus disease 2019, we aimed to find out whether HRV prevailed among children in 2020 and demonstrate the details of the epidemiological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 43 publications
4
16
0
Order By: Relevance
“…A study conducted by Dr. Zhang et al 17 observed a sharp increase in the positive rate of HRV in Beijing, China, and reasonably assumed to be explained by the reopening of the primary and secondary schools in Beijing. Studies conducted in Shanghai, China, America, and German showed that HRV stayed low in the first quarter of 2020, and raised rapidly in June, matches our study, and observed relatively higher morbidity in the rest of the year 18–21 . Another study 22 conducted in Southampton, UK, gave a theory that the HRV was mainly found in children and adolescents who were the major reservoir for HRV infection, social distancing and face masks are not effective in preventing transmission of HRV, with “ Back‐to‐School Upper Respiratory Infection ” effect, 23 the risk of HRV transmission surges after schools reopening.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A study conducted by Dr. Zhang et al 17 observed a sharp increase in the positive rate of HRV in Beijing, China, and reasonably assumed to be explained by the reopening of the primary and secondary schools in Beijing. Studies conducted in Shanghai, China, America, and German showed that HRV stayed low in the first quarter of 2020, and raised rapidly in June, matches our study, and observed relatively higher morbidity in the rest of the year 18–21 . Another study 22 conducted in Southampton, UK, gave a theory that the HRV was mainly found in children and adolescents who were the major reservoir for HRV infection, social distancing and face masks are not effective in preventing transmission of HRV, with “ Back‐to‐School Upper Respiratory Infection ” effect, 23 the risk of HRV transmission surges after schools reopening.…”
Section: Discussionsupporting
confidence: 77%
“…Studies conducted in Shanghai, China, America, and German showed that HRV stayed low in the first quarter of 2020, and raised rapidly in June, matches our study, and observed relatively higher morbidity in the rest of the year. 18 , 19 , 20 , 21 Another study 22 conducted in Southampton, UK, gave a theory that the HRV was mainly found in children and adolescents who were the major reservoir for HRV infection, social distancing and face masks are not effective in preventing transmission of HRV, with “ Back‐to‐School Upper Respiratory Infection ” effect, 23 the risk of HRV transmission surges after schools reopening. On the other hand, Dr. Leung et al 24 conducted experiments and proved that there was no significant difference in filtering or protection effect of HRV between wearing a face mask or not, indicating that wearing masks cannot effectively protect the population from the HRV infection.…”
Section: Discussionmentioning
confidence: 99%
“…For further genotyping, 403 nasopharyngeal aspirates were collected randomly from the RSV-positive inpatients from October 2019 to October 2021. Severe cases were defined by experienced clinicians according to the World Health Organization (WHO)‘s latest definitions of severe LRTIs ( Vanker et al, 2017 ; Jia et al, 2022 ). Demographic information and medical data for each patient were collected from electronic records in the hospital.…”
Section: Methodsmentioning
confidence: 99%
“…As a typical seasonal virus, RSV usually peaks in winter and declines by early spring in most temperate countries, with a median duration of 10–21 weeks ( Staadegaard et al, 2021 ). However, the unexpected coronavirus disease 2019 (COVID-19) pandemic has exerted extraordinary changes to community behavior at a population level and remarkably restricted the prevalence of respiratory pathogens ( Liu et al, 2021 ; Jia et al, 2022 ). However, along with the normalization of the COVID-19 epidemic control, an atypical reemergence of RSV was reported in various places ( Agha and Avner, 2021 ; Foley et al, 2021 ; Government of Western Australia, 2021 ; Ujiie et al, 2021 ; Camporesi et al, 2022 ; Eden et al, 2022 ; Saravanos et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…During the 2019-2021 SARS-CoV-2 pandemic, social distancing and masking protocols to reduce coronavirus transmission resulted in significantly lower numbers of respiratory syncytial virus and influenza virus infections. This was not the case for HRV (2)(3)(4). Rhinovirus infections are currently an inevitable part of life for humans of all ages, with an expected one to two rhinovirus infections per year over an average lifespan (5).…”
Section: Introductionmentioning
confidence: 99%